Adaptability of winter wheat Dongnongdongmai 1 (Triticum aestivum L.) to overwintering in alpine regions. (26th January 2021) - Bao, Y.; Yang, N.; Meng, J.; Wang, D.; Fu, L.; Wang, J.; Cang, J.
Abstract: Long winters led to a one‐crop‐a‐year cultivation system until the winter wheat Dongnongdongmai 1 (Dn1) was successfully cultivated in northeast China. This crop variety is resistant to extremely low temperatures (−35 °C). To better understand the adaptability of winter wheat Dn1 to low temperatures, gas chromatography time‐of‐flight mass spectrometry (GC‐TOF/MS) and metabolomics analysis was conducted on the tillering nodes of winter wheat during the overwintering period. Enzyme‐regulating genes of the metabolic products were also quantitatively analysed. The metabolomic results for the tillering nodes in the overwintering period showed that disaccharides had a strong protective effect on winter wheat Dn1. Amino acid metabolism ( i.e . proline, alanine and GABA) changed significantly throughout the whole wintering process, whereas organic fatty acid metabolism changed significantly only in the late stage of overwintering. This result indicates that the metabolites used by winter wheat Dn1 differ in different overwintering stages. The relationship between field temperature and metabolite changes in winter wheat Dn1 during overwintering periods is discussed, and disaccharides were identified as the osmotic stress regulators for winter wheat Dn1 during the overwintering process, as well as maintenance of the carbon and nitrogen balance by monosaccharides, amino acids and lipids for cold resistance. Abstract : This study identified disaccharides as the osmotic stress regulators of winter wheat Dn1 during the overwintering process, as well as the carbon and nitrogen balance maintained by monosaccharides, amino acids, and lipids for cold resistance.